A progenitor candidate for the type II-P supernova SN 2018aoq in NGC 4151 - O'Neill D.; Kotak R.; Fraser M.; Sim S. A.; Benetti S.; Smartt S. J.; Mattila S.; Ashall C.; Callis E.; Elias-Rosa N.; Gromadzki M.; Prentice S. J. (EDP Sciences, 2022)
We present our findings based on pre- and post-explosion data of the type II-Plateau SN 2018aoq that exploded in NGC 4151. As distance estimates to NGC 4151 vary by an order of magnitude, we utilised the well-known correlation between ejecta velocity and plateau brightness, i.e. the standard candle method, to obtain a distance of 18.2 ± 1.2 Mpc, which is in very good agreement with measurements based on geometric methods. The above distance implies a mid-plateau absolute magnitude of MV50 = - 15.76 ± 0.14 suggesting that it is of intermediate brightness when compared to IIP SNe such as SN 2005cs at the faint end, and more typical events such as SN 1999em. This is further supported by relatively low expansion velocities (Fe IIλ5169 ˜ 3000 km s-1 at +42 d). Using archival HST/WFC3 imaging data, we find a point source coincident with the supernova position in the F350LP, F555W, F814W, and F160W filters. This source shows no significant variability over the ˜2 month time span of the data. From fits to the spectral energy distribution of the candidate progenitor, we find log(L/L⊙) ˜ 4.7 and Teff ˜ 3.5 kK, implying an M-type red supergiant progenitor. From comparisons to single and binary star models, we find that both favour the explosion of a star with a zero-age main sequence mass of ˜10 M⊙.